On Generalized Derivations of BCI-Algebras and Their Properties - L. Kamali Ardekani; B. Davvaz (Journal of Mathematics)
We introduce the concept of (f,g)-derivations of BCI-algebras and we investigate some fundamental properties and establish some results on (f,g)-derivations. Also, we treat to generalization of right derivation and left derivation of BCI-algebras and consider some related properties.